2011
DOI: 10.1002/joc.2069
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Cool Island in the Sahelian city of Ouagadougou, Burkina Faso

Abstract: ABSTRACT:Relatively little is known about the urban climate processes of the fastest growing cities in the world today. Described in this paper are urban-rural and intra-urban variations in air temperature and humidity in one of these cities; Ouagadougou, Burkina Faso. Measurements were collected from car traverses and fixed site measurements during two field studies. The aim of the study was to determine the influence of land use on the urban climate in this hot-dry region, with a focus on the role of vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Site 5 DMN is used as a reference station in our study and it was also used as reference by Offerle et al (2005), Eliasson et al (2009) andLindén (2010). Details of the instruments are given in Table 2.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Site 5 DMN is used as a reference station in our study and it was also used as reference by Offerle et al (2005), Eliasson et al (2009) andLindén (2010). Details of the instruments are given in Table 2.…”
Section: Study Areamentioning
confidence: 99%
“…However, the LCZs may also be considered as source areas. In Ouagadougou, Lindén (2010) obtained the best relationship between intra-urban temperatures and source areas with a radius of 400 m. This is smaller than the circle with 500 m radius used by Chow and Roth (2006) but a larger area than the 300 m grid used by Hart and Sailor (2009) and Yokobori and Ohta (2009) or 180 m sector in the wind direction used by Murphy et al (2010). Li and Roth (2007) used both 100 and 500 m radius and found best correlation between vegetation cover and UHI intensity for the smaller circle.…”
Section: Source Areas -Lczmentioning
confidence: 99%
“…According to a review by Caird et al (2007), night-time transpiration rates of various plants, including trees, usually amount to 5-15 % of the daytime values. While not directly measured, evening evapotranspiration has also been suggested by Lindén (2011) and Holmer et al (2013) as a reason behind intensive nocturnal cooling of densely vegetated areas in the tropical city of Ouagadougou, Burkina Faso. The rapid cooling of vegetated areas in Ouagadougou around sunset, in the so-called Phase 1 of nocturnal cooling (Holmer et al 2007), was accompanied by an increase of specific humidity not observed at non-vegetated sites, which cooled more slowly.…”
Section: Introductionmentioning
confidence: 95%
“…Although numerous studies of urban climate have shown that cooler places within the city are closely connected to an increased vegetation cover (Alavipanah et al 2015;Fan et al 2015;Harlan et al 2006;Lindén 2011;Middel et al 2012;Norton et al 2015), the diurnal variations as well as influence of changing weather conditions on the transpiration-induced cooling are still unclear. For example, cooling was strongest in the afternoon in irrigated parks and parks in humid climates (Jonsson 2004;Potchter et al 2006;Spronken-Smith and Oke 1998).…”
Section: Introductionmentioning
confidence: 99%